The Students’ Creative Thinking Skills on Literacy Numeracy Concepts - Lasia Agustina; Zaenuri Zaenuri; Isnarto Isnarto; Dwijanto Dwijanto (International Conference on Science, Education, and Technology, 2021)
The 21st-century citizens should have creative thinking skills with literature problems. This thinking has three components: novelty, flexibility, and fluency. This research aims to determine how the students’ creative thinking skills through questions with numeric literacy concepts. This research is descriptive qualitative research with the triangulated data. The subjects were the students of the University of Indraprastha PGRI, Southern Jakarta. After taking the test, the researchers categorized the creative thinking skills into creative, average, and not creative categories. The results showed a new component supported the students’ creative thinking skills about the numeric literacy concept. It was the communication. Previous studies showed four components to measure individuals’ creative thinking skills on the numeric literacy concepts. They were communication, novelty, flexibility, and fluency. This research concluded that the student's creative thinking skills on the numerical literacy concept questions would be more observable if the communication component existed.